2020
DOI: 10.1088/2053-1591/ab6262
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of flexible and highly stable graphene oxide-silver nanowire hybrid transparent conductive electrode

Abstract: The flexible and highly stable graphene oxide (GO)/silver nanowires (AgNWs) hybrid transparent conductive electrode (TCE) was fabricated by coating AgNWs and GO inks on the surface of polyethylene terephthalate (PET) using a Meyer rod. The as-prepared GO/AgNWs hybrid TCE with a GO concentration of 0.75 mg·ml −1 exhibits excellent optoelectronic performances with a sheet resistance of 25 Ω·sq −1 , a transmittance of 87.6% at 550 nm, and a lower surface roughness with a root mean square (RMS) roughness value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Sheet resistance versus optical transmittance at 550 nm for rGO/Ag NW films and previous reported Ag NW-based transparent conductive films are plotted in Fig. 3f and Table 1 [9,17,19,20,[35][36][37][38][39][40][41]. The rGO/Ag NW films combine the merits of high transmittance and low sheet resistance.…”
Section: Optical Transmittance and Electrical Conductivitymentioning
confidence: 75%
“…Sheet resistance versus optical transmittance at 550 nm for rGO/Ag NW films and previous reported Ag NW-based transparent conductive films are plotted in Fig. 3f and Table 1 [9,17,19,20,[35][36][37][38][39][40][41]. The rGO/Ag NW films combine the merits of high transmittance and low sheet resistance.…”
Section: Optical Transmittance and Electrical Conductivitymentioning
confidence: 75%
“…In addition, we compared the photoelectric performance of the hybrid TCE with the other transparent electrodes reported recently, and the data was displayed in Table S1 in the Supporting Information. [ 8,26–29 ] It indicated that the composite electrodes had relatively low sheet resistance and high transmittance.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, hybrid electrodes comprising AgNWs‐graphene oxide (GO) and AgNWs‐mono layer graphene (MLG) from CVD have been widely investigated and applied to numerous optoelectronic devices. [ 15–167 ] As shown in Table 4, significant surface‐roughness reduction by applying these materials is achievable. The GO dispersion induced...…”
Section: Problems Of Agnws In Solar Cellsmentioning
confidence: 99%